Synthesis of cyanolide A and the neopeltolide core structure - Lek, Tee Guan (2016)
The introduction of the chapter highlights the application of natural product synthesis via synthetic strategies that have been developed over the past decades. The oxa-Michael cyclisation reaction have been one of the most frequently used reaction for the synthesis of tetrahydropyran rings in natural products. This introduction would highlight the different strategies and the application of the oxa-Michael cyclisation reaction in the synthesis of natural products. Chapter two describes the synthesis of cyanolide A, which was isolated from the extracts of cyanobacteria; Lyngbya bouillonii. In our synthesis of cyanolide A, the oxaMichael cyclisation will be utilized to form the tetrahydropyran core ring and the approach taken to overcome the difficulties with the gem-dimethyl group in the cyanolide A structure. Chapter three describes the formal synthesis of (+)-neopeltolide core structure, the application of the 2-directional synthesis approach will be applied to synthesize the tetrahydropyran ring using the cross-metathesis/oxa-Michael cyclisation reaction. The formation of the (+)-neopeltolide core ring would utilise the Kulinkovich reaction and Barbier reaction to furnish the (+)-neopeltolide core structure.